Characterisation of Chemical Constitutes and Spermatogenic Activity of Ushir (Vetiveria Zizanioides Linn) versus Ikshu (Saccharum Officinarum Linn) in Male Wistar Rats: A Research Protocol - Akshay Sudhir Pargaonkar; Jaymala Jadhav; Bhagyashree Ratan Jibkate; Minakshi Urkude (Journal of Clinical and Diagnostic Research)
Introduction: In men, infertility may results from impaired sperm quality, quantity and abnormalities. In Ayurveda, there are various herbal medicines that are stated to possess effective aphrodisiac (Vajikarana) properties and purification of the semen (shukrashodhana) activities that are relevant to both aphrodisiac and spermatogenic effects. One such herb that possesses the purification of semen (shukrashodhangana) and is often used is Ushir (Vetiveria zizanioides) and Ikshu (Sugarcane) (Saccharum officinarum). Standardisation of Ayurvedic medicines at the pharmaceutical and analytical levels is important for proceeding with preclinical or clinical studies. The outcomes of animal research have helped consider the drug’s benefits and drawbacks. Need of the study: There is a need to evaluate this fact. Ikshu swaras (juice of S. officinarum) (Juice of Sugarcane) has a shelf life of one hour, while Ushir churna (powder of V. zizanioidis) is easily available and has a shelf life of two years. If both drugs have similar actions, then Ikshu (sugarcane) can be replaced by Ushir. The phytochemical characterisation of Indian species of these two drugs also needs to be discovered, as it may provide detailed information regarding chemical constituents and may explore additional utility. Aim: To evaluate the characterisation of chemical constituents and the spermatogenic activity of Ushir (Vetiveria zizanioides) versus Ikshu (Saccharum officinarum) (sugarcane) in male Wistar rats. Materials and Methods: An experimental study will be conducted at the preclinical animal research facility of Datta Meghe Higher Education and Research (DIMHER), Wardha, Maharashtra, India (DU) from January 2022 to January 2025. The preparation of the drugs will be standardised as per Ayurvedic Pharmacopoeia of India (API) in the analytical laboratory of Dattatray Rasashala of MGACH&RC Salod, Wardha, Maharashtra, India. Five groups will be formed, each consisting of six male Wistar rats. The groups will include a normal control group, a disease control group, a standard control group and two test groups. Parameters that will be assessed include sperm morphology, sperm motility, pH, agglutination, sperm count, serum testosterone levels and histopathology. The experimental study will be conducted as per Organisation for Economic Cooperation and Development (OECD) guidelines. For statistical analysis, the mean and standard deviation of the treated groups will be calculated using an unpaired t-test and one-way Analysis of Variance (ANOVA) analysis, with a significance level set at p<0.05.